Monitoring and Evaluating the Poverty Impacts of Agricultural Water Investments - Sur, Mona (World Bank, Washington, DC, 2012)
Monitoring and evaluating (M&E) the poverty impact of agricultural water investments may allow some conclusions about returns on different types of investments and their contributions to poverty reduction. This paper recommends the following: involve beneficiaries early in the M&E process -- broad consultations and early involvement of users in the design and implementation of the M&E system will do much to build consensus and ownership; use beneficiary self-assessments and other participatory approaches so that assessments can be made midcourse -- there may be a long time lag in realizing a reduction in poverty from agricultural water-related projects, and the poverty impact often cannot be evaluated until well after a project ends; keep the number of indicators collected within manageable proportions; and ensure that a good baseline survey is undertaken -- without a proper baseline, it is difficult to monitor progress and evaluate the impacts of investments.